Rho family GTPases, Rac and Cdc42, control the localization of neonatal dentate granule cells during brain development. Issue 7 (25th November 2018) - Ito, Hidenori; Morishita, Rika; Mizuno, Makoto; Tabata, Hidenori; Nagata, Koh‐ichi
Abstract: The hippocampus is generally considered as a brain center for learning and memory. We have recently established an electroporation‐mediated gene transfer method to investigate the development of neonatal dentate granule cells in vivo. Using this new technique, we introduced knockdown vectors against Rac1 small GTPase into precursors for dentate granule cells at postnatal day 0. After 21 days, Rac1‐deficient cells were frequently mispositioned between the granule cell layer (GCL) and hilus. About 60% of these mislocalized cells expressed a dentate granule cell marker, Prox1. Both the dendritic spine density and the ratio of mature spine were reduced when Rac1 was silenced. Notably, the deficient cells have immature thin processes during migrating in the early neonatal period. Knockdown of another Rac isoform, Rac3, also resulted in mislocalization of neonatally born dentate granule cells. In addition, knockdown of Cdc42, another Rho family protein, also caused mislocalization of the cell, although the effects were moderate compared to Rac1 and 3. Despite the ectopic localization, Rac3‐ or Cdc42‐disrupted mispositioned cells expressed Prox1. These results indicate that Rho signaling pathways differentially regulate the proper localization and differentiation of dentate granule cells.